PENGARUH BIMBINGAN ORANG TUA TERHADAP KEBERHASILAN BELAJAR BELAJAR ANAK DI RUMAH PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI TINGKAT SEKOLAH DASAR DESA BANBARU GILIGENTING SUMENEP - Elis Tafiya; Syafrawi Syafrawi (Journal of Education Partner, 2022)
There are two problems in this study, namely, first, whether or not there is an influence of parental guidance on the success of children's learning at home in Islamic Religious Education Subjects at the Banbaru Giligenting Sumenep Village Elementary School Level in 2020. Second about How Much Influence Parental Guidance has on Children's Learning Success at Home in Islamic Religious Education subjects at the Banbaru Giligenting Sumenep Village Elementary School Level 2020. The design of this study uses Quantitative research while the Research Engineering uses correlational techniques and the instruments used in data collection are questionnaires, while supporting instruments are interviews, observations and documentation. The formula used in this study is to use the Product Moment correlation formula. The results showed that: 1) there was an influence of parental guidance on the success of children's learning at home in Islamic Religious Education subjects at the Banbaru Giligenting Sumenep Village Elementary School level 2020 this is evident from the results of the analysis obtained 0.88 which is greater than the criticism price "r" Product Moment both in 5% and 1% confidence intervals where N-nr = 62-2 = 60 obtained a value of 0.25 at a significant level of 5% and 0.21 at a significant level of 1%. 2) The influence of parental guidance on the success of children's learning at home in the subject of Islamic Religious Education at the Elementary School level of Banbaru Gili Genting Sumenep Village 2020. Including High category. This is evidenced after the working r of 0.88 entered in the table is in the amgka range between 0.70-0.90 with the category High. Based on parental guidance on the success of children's learning at home in Islamic religious education subjects at the Banbaru Giligenting Sumenep Village Elementary School level 2020 is the right way to get children's participation at home as a whole or individually.